2021
DOI: 10.1249/mss.0000000000002658
|View full text |Cite
|
Sign up to set email alerts
|

Female Athletes Genetically Susceptible to Fatigue Fracture Are Resistant to Muscle Injury: Potential Role of COL1A1 Variant

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In contrast, a previous study suggested that the CC genotype carriers had significantly lower lumbar spine BMD than AA genotype carriers [13]. The CC genotype in COL1A1 rs1107946 polymorphism may be a risk factor for low BMD and fatigue fractures [13,[37][38][39]. Therefore, there is a trade-off between muscle and bone injury: the A allele in COL1A1 is associated with higher BMD, while the C allele decreases the risk of muscle injury.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In contrast, a previous study suggested that the CC genotype carriers had significantly lower lumbar spine BMD than AA genotype carriers [13]. The CC genotype in COL1A1 rs1107946 polymorphism may be a risk factor for low BMD and fatigue fractures [13,[37][38][39]. Therefore, there is a trade-off between muscle and bone injury: the A allele in COL1A1 is associated with higher BMD, while the C allele decreases the risk of muscle injury.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study reported an association between COL1A1 rs1107946 polymorphism and flexibility (e.g., muscle stiffness) [ 13 ]. The study suggested that the C allele (CC + AC genotype) of COL1A1 rs1107946 polymorphism shows lower muscle stiffness than the AA genotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations